La responsabilidad social empresarial y su evolución financiera en el hotel MANTAHOST de la ciudad de Manta - Santana Loor, Jacqueline Jamileth (2022)
The objective of this research was to analyze Corporate Social Responsibility (hereinafter CSR) and its financial evolution in the Mantahost hotel in Manta city. It was a bibliographical and field research, where the analytical, descriptive and deductive method was integrated; followed by the Delphi method for the validation of the survey questionnaire, applying the Likert scale valued in a range from 1 to 5. This inquiry is made up of three phases: the first consisted of determining the indicators of the social, economic and environmental CSR and financial indicators, then evaluate the level of compliance with Corporate Social Responsibility and the financial evolution of the Mantahost hotel and finally, an action plan for Corporate Social Responsibility was proposed in the financial evolution of the Mantahost hotel. The execution of the same, resulted in the hotel company for its category, maintains integrated compliance with CSR in its activities, however, it was found through the application of financial indicators that there are certain shortcomings that indicate that the company, is not being socially responsible, therefore, an action plan was applied to improve deficiencies through the 5w+1h matrix. It is concluded that CSR greatly influences the financial evolution of organizations, since it provides valid information to know their financial situation, allowing them to identify their strengths and weaknesses, to consecutively work on them, taking and applying the appropriate strategic decisions.